Apical sparing strain pattern observed in danon disease: insights from a global registry. (25th November 2020) - Bui, Q; Ma, G; Kraushaar, M; Escobedo, V; Le, B; Covarrubias, E; Brambatti, M; Kahn, A; Bougault, C; Hong, K; Taylor, M; Adler, E
Abstract: Background: Danon Disease (DD) is a rare X-linked autophagic disorder due to mutations in the Lysosomal Associated Membrane Protein 2 (LAMP-2) gene and causes severe cardiac manifestations. Measurement of longitudinal strain (LS) has been shown to provide diagnostic insights into different etiologies of hypertrophic cardiomyopathies compared to conventional echocardiographic parameters. Purpose: The aim of this study was to describe the pattern of global and regional LS in DD. Methods: A retrospective, international registry, using medical records provided by patients, was formed to describe the natural history of DD. Complete echocardiogram images were available for review and LS was analyzed globally and regionally (basal, mid, apex). Results: A total of eighteen DD patients (male 72%, mean age 17.2±10 years) had sufficient quality echocardiographic images for both traditional and myocardial strain evaluation. Notable traditional echocardiographic parameters included a mean EF of 60±11%, LV mass index 200±159 g/m 2, intraventricular septal diameter 17.7±10.3 mm, LV posterior wall diameter 16.1±7.7 mm, LA volume index 21.9±13 mL/m 2 . Global longitudinal strain was reduced with a mean of −12.1±4.9% with an observed regional strain gradient: apex (−16.6±6.6%), mid (−10.9±4.7%) and basal (−9.2±4.5%). Bull's eye plot patterns reflected an apical sparing pattern that was similar to that described in cardiac amyloidosis. Conclusion: In this DD cohort, we describe for the first time a strain pattern characterized by reduction in global longitudinal strain with apical sparing, which was originally pathognomonic for cardiac amyloidosis. This strain pattern in conjunction with a paradoxically normal LA volume may discriminate patients with DD from other hypertrophic conditions. Funding Acknowledgement: Type of funding source: None